2017
DOI: 10.1111/nph.14868
|View full text |Cite
|
Sign up to set email alerts
|

Successive evolutionary steps drove Pooideae grasses from tropical to temperate regions

Abstract: Angiosperm adaptations to seasonally cold climates have occurred multiple times independently. However, the observation that less than half of all angiosperm families are represented in temperate latitudes suggests internal constraints on the evolution of cold tolerance/avoidance strategies. Similar to angiosperms as a whole, grasses are primarily tropical, but one major clade, subfamily Pooideae, radiated extensively within temperate regions. It is posited that this Pooideae niche transition was facilitated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 80 publications
2
33
0
Order By: Relevance
“…S2B). These results indicate that the evolution of cold acclimation evolved at least partly independently in separate lineages and are in line with recent work on transcriptional responses to vernalization in Pooideae (McKeown et al, 2016;Zhong et al, 2018).…”
Section: Cold Acclimation Evolved Independently In Separate Lineagessupporting
confidence: 91%
“…S2B). These results indicate that the evolution of cold acclimation evolved at least partly independently in separate lineages and are in line with recent work on transcriptional responses to vernalization in Pooideae (McKeown et al, 2016;Zhong et al, 2018).…”
Section: Cold Acclimation Evolved Independently In Separate Lineagessupporting
confidence: 91%
“…This hypothesis is supported by two recent studies. In a study of three Pooideae species, Zhong, Robbett, Poire, & Preston (2018) identified several gene clusters exhibiting conserved cold response, many of which had previously been characterized as ancient stress response genes. Another study found 16 cold-responsive genes that exhibited conserved expression in five distantly related Pooideae species (Schubert, Grønvold, Sandve, Hvidsten, & Fjellheim, 2019).…”
Section: Frost Tolerance and Ancestral Nichementioning
confidence: 99%
“…This hypothesis is supported by two recent studies. In a study of three Pooideae species, Zhong, Robbett, Poire, & Preston (2017) identified several gene clusters exhibiting conserved cold response, many of which had previously been characterized as ancient stress response genes. Another study found sixteen cold responsive genes that exhibited conserved expression in five distantly related Pooideae species (Schubert et al, unpublished).…”
Section: Did the Pooideae Ancestor Live In Cold Microhabitats?mentioning
confidence: 99%